Implementation of the BUGEMM (Culture of Reading and Writing) Program in Training Students' Scientific Writing Skills - Winda Andini; Febriyanti; Ani Marlia (PAI RAFAH, 2026)
The Budaya Gemar Baca dan Tulis (BUGEMM) Program was developed by SMA Plus Negeri 17 Palembang as a strategy to strengthen the school's literacy culture and enhance students' scientific writing skills. This study aims to explore the implementation of the BUGEMM Program and to identify its supporting and inhibiting factors. The research employed a qualitative field-based approach. Data were collected through on-site observations, in-depth interviews, and document analysis. Participants were selected purposively and included the vice principal for curriculum affairs, the BUGEMM program coordinator, mentor teachers, and students involved in the program. Data analysis was conducted through data condensation, data display, and conclusion drawing. The findings indicate that the BUGEMM Program is implemented in an organized and systematic manner through several stages, including program socialization, appointment of supervising teachers, student grouping, topic selection, reference searching, outline preparation, drafting, and scientific paper presentation. Supervising teachers play a crucial role by providing guidance, intensive supervision, and continuous evaluation throughout the writing process. Supporting factors include strong school policies, adequate literacy facilities, teacher competence, parental involvement, and consistent scheduling. Meanwhile, inhibiting factors consist of low student engagement in literacy activities and limited parental support at home. Overall, the results demonstrate that the BUGEMM Program contributes positively to improving students' scientific writing skills and strengthening the literacy culture within the school environment.